Coupling fraction model to interpret the motion of non-fully coupled strike-slip faults - Zou, Zhenyu; Jiang, Zaisen; Wu, Yanqiang; Cui, Yueju; Tang, He (Frontiers in Earth Science, 2023)
Despite coupling fraction being extensively used in the interseismic period, the coexistence of locking and creeping mechanisms and correlation between the coupling fraction and locking depth remain poorly understood because of the lack of a physical model. Therefore, to overcome these limitations, in this study, we propose a coupling fraction model for the interpretation of the motion of non-fully coupled strike-slip faults based on the classic two-dimensional strike-slip fault model and superposition principle. The model was constructed using numerous tiny, alternating creeping and locking segments. The deformation produced by the model is the same as that of the classic two-dimensional strike-slip fault, except for the scale factor. The model and definition of coupling fraction can be perfectly integrated. Based on the model, a varying decoupled fraction with depth model was put forward, which considers depth-dependent coupling fraction. The two models provided deep insights into deformation characteristics of quasi-arctangent curves produced by non-fully coupled strike-slip faults and the local and macroscopic ones of fault locking in the interseismic period.